Analisis dampak pembelajaran dalam jaringan (daring) pada kompetensi pedagogik dan profesional guru sekolah dasar - Artini Tyas Utami; Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri (Universitas Sebelas Maret, 2021)
This study aims to (1) describe the impact of online learning on the pedagogicalcompetence of grade 1 teachers at SDN Mangkubumen Lor No 15 Surakarta during the pandemic period; (2) to describe the impact of online learning on the professional competence of grade 1 teachers at SDN Mangkubumen Lor No 15 Surakarta during the pandemic period. This research used descriptive qualitative research methods with a case study approach. The data collection technique used the interview method and documentation study. The sampling technique used purposive sampling, namely grade 1 teachers of SDN Mangkubumen Lor No. 15 This study used Miles and Huberman field data analysis techniques with 4 steps, namely data collection, data reduction, data presentation, and drawing conclusions. The validity test used is using the Gregory technique analysis through the assessment of 4 experts. The results of the study show that the impact of online learning during the pandemic has resulted in low pedagogical and professional competence of primary school teachers, seen from several indicators that each competency has not been implemented by teachers optimally